Informant-Reported Cognitive Decline is Associated with Objective Cognitive Performance in Parkinson's Disease. (9th May 2021) - Nakhla, Marina Z.; Holiday, Kelsey A.; Filoteo, J. Vincent; Zlatar, Zvinka Z.; Malcarne, Vanessa L.; Lessig, Stephanie; Litvan, Irene; Schiehser, Dawn M.
Abstract: Objective: The utility of informant-based measures of cognitive decline to accurately describe objective cognitive performance in Parkinson's disease (PD) without dementia is uncertain. Due to the clinical relevance of this information, the purpose of this study was to examine the relationship between informant-based reports of patient cognitive decline via the Informant Questionnaire of Cognitive Decline in the Elderly (IQCODE) and objective cognition in non-demented PD controlling for cognitive status (i.e., mild cognitive impairment; PD-MCI and normal cognition; PD-NC). Method: One-hundred and thirty-nine non-demented PD participants (PD-MCI n = 38; PD-NC n = 101) were administered measures of language, executive function, attention, learning, delayed recall, visuospatial function, mood, and motor function. Each participant identified an informant to complete the IQCODE and a mood questionnaire. Results: Greater levels of informant-based responses of patient cognitive decline on the IQCODE were significantly associated with worse objective performance on measures of global cognition, attention, learning, delayed recall, and executive function in the overall sample, above and beyond covariates and cognitive status. However, the IQCODE was not significantly associated with language or visuospatial function. Conclusions: Results indicate that informant responses, as measured by the IQCODE, may provide adequate information on a wide range of cognitive abilities in non-demented PD, including those with MCI and normal cognition. Findings have important clinical implications for the utility of the IQCODE in the identification of PD patients in need of further evaluation, monitoring, and treatment.